2020
DOI: 10.1177/0266242620958898
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital presence and investment network signals on the internationalisation of small firms

Abstract: This article proposes a network signalling theory approach to analyse small firm internationalisation in the digital economy. We use a data set of 4446 small- and medium-sized firms extracted from Funderbeam and logit regression models to test five hypotheses about internationalisation. Exploring a firm’s digital presence indicates that the number of social media followers is a better indicator of internationalisation than website traffic, highlighting the importance of engagement signals in the digital space.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 120 publications
0
10
0
Order By: Relevance
“…The firms' website traffic (measured as monthly unique website visits, Kotha et al, 2001) was chosen as a relevant IV for the firms' internationalization speed because it encourages e-commerce firms to internationalize (e.g., Benmamoun et al, 2019). Website traffic is an indicator of e-commerce firms' customer relations and their promotional effectiveness in terms of foreign website access and search engine placement (e.g., Kromidha & Robson, 2021). Consequently, higher website traffic enables firms to establish partnerships and attract consumers, which accelerates the penetration of foreign markets (Kotha et al, 2001).…”
Section: Measurementmentioning
confidence: 99%
“…The firms' website traffic (measured as monthly unique website visits, Kotha et al, 2001) was chosen as a relevant IV for the firms' internationalization speed because it encourages e-commerce firms to internationalize (e.g., Benmamoun et al, 2019). Website traffic is an indicator of e-commerce firms' customer relations and their promotional effectiveness in terms of foreign website access and search engine placement (e.g., Kromidha & Robson, 2021). Consequently, higher website traffic enables firms to establish partnerships and attract consumers, which accelerates the penetration of foreign markets (Kotha et al, 2001).…”
Section: Measurementmentioning
confidence: 99%
“…Secondly, the corporate websites of Portuguese SMEs are digital tools with a minimum of functionalities that allow them to communicate at a low level. For that reason, it has been found that Portuguese SMEs need to make changes in their digital communications strategy with their publics in order to be more competitive [51] and to reach a high level of maturity in the context of their digital communication.…”
Section: Discussionmentioning
confidence: 99%
“…Liu (2023) maintained that due to the setback in universal economic rescue, obstinate international situation uncertainties, and an increase in isolationism, China has consistently upheld a reasonable level of sincerity and actively engaged in international assistance to the outside world, most especially African countries. Interestingly, high-profile educational organisations in China have willingly extended their participation in foreign markets, by accelerating their expedition to penetrating the global internationalisation sphere (Maldonado-Maldonado & Bassett, 2014;Kromidha & Robson, 2021). However, organisations face several encounters due to reasons such as capability, capital, and access to other resources (Dekel-Dachs et al, 2021).…”
Section: Venture Capital On Internationalisationmentioning
confidence: 99%